Numerical Solution to Determine Optimum Oil Production Rate - (NIM 12205061); Pembimbing: Dr. Ir. Pudjo Sukarno, SUWANTO
In this paper, we will discuss about numerical solution to determine optimum oil production rate by substitute TPR equation into IPR equation. Because of IPR and TPR equations depend on term oil rate, so this equation system will be solved iteratively. Oil rate and pressure yielded are the intersection between IPR and TPR curves. The yielding of the intersection will be compared with optimum oil rate from commercial software as a validation. Besides this, also done sensitivity analysis to input data to know range of input data tolerantly in a program.